Addie meets max - Robins, Joan (New York : HarperCollins Publishers Inc, 1984)
Addie discovers that the new boy next door, Max and his dog are not so terrible when she helps Max bury his newly lost tooth.
Keywords: Children's stories, American; Friendship--Fiction